Evaluasi dan Perbaikan Desain Antarmuka Pengguna pada Aplikasi Mobile Halal Tracking dengan Menggunakan Metode Heuristic Evaluation - Citra Mahardhika Dewi Murti; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tourist areas in various regions visited by the largest tourists in the world. Indonesia has a variety of tours that are supported by the development of the technology developed to help people get information. Halal Tracking is a mobile application to facilitate the public to retrace tourist destination information in Indonesia to support Islamic tourism which is now a trendsetter among international tourists where the public offers tourists in regions that provide anxiety to get halal-supported products. This research helps develop problems in this mobile application, making the evaluation results can be developed. Evaluation results are needed in further development for better mobile applications. Heuristic Method Evaluation in its use will be carried out the testing process as much as 2 times the evaluation with the help of the evaluator to obtain the perspective of the problem found based on the established heuristic principles. There were 36 problems found in the evaluation, but after consolidation, there were 26 problems. The average evaluation results are 2.96. Furthermore, the design is designed, created using the guidelines on the mobile application. Problems found in the further evaluation were 4 problems. Design improvements made to continue making an average of 1.5. As such, the results of the renewal referred to by design improvements for problems from the Halal Tracking mobile application are better than the initial design..